PENGARUH LITERASI PAJAK TERHADAP AKSES PEMBIAYAAN PERBANKAN DENGAN KEPATUHAN WAJIB PAJAK SEBAGAI VARIABEL MEDIASI PADA UMKM GERABAH DI DESA WISATA KASONGAN: PENGARUH LITERASI PAJAK TERHADAP AKSES PEMBIAYAAN PERBANKAN DENGAN KEPATUHAN WAJIB PAJAK SEBAGAI VARIABEL MEDIASI PADA UMKM GERABAH DI DESA WISATA KASONGAN - Vallentiasafita Tutu Sari; Rochmad Bayu Utomo (ITB AAS Indonesia Surakarta, 2026)
MSMEs play a strategic role in the national economy, but still face obstacles in tax literacy and access to formal financing, including pottery MSMEs in Kasongan Tourism Village, which show a relatively low level of tax compliance. The implementation of the Coretax Administration System as part of tax modernization is expected to improve taxpayer compliance based on the theory of Financial Intermediation. This study aims to examine the effect of tax literacy on access to bank financing, with taxpayer compliance as a mediating variable in pottery MSMEs in Kasongan Tourism Village. The study used a quantitative approach through a questionnaire survey of 60 respondents selected using a purposive sampling technique. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the help of SmartPLS 4. The results showed that tax literacy had a positive and significant effect on taxpayer compliance. The mediation test proved that taxpayer compliance significantly mediated the effect of tax literacy on access to bank financing. This finding emphasizes the importance of improving tax literacy in strengthening the financial credibility of MSMEs in order to expand access to bank financing.